SICHJO A GENRE THAT CALLS FROM LUXURY TO NATURE - Iroda San’at kiziTohirova (American Journals, 2023)
This article deals with the genre of “Sichjo” that originated in Korea during the Joseon (Li) Literature period (1392-1910). This genre is considered a lyrical genre with a certain image of excitement and experience, which embodies the traditions of Korean folklore and the three religious-philosophical teachings of the peoples of the Far East (Confucianism, Buddhism and Taoism).
Keywords: Joseon, history of Korean literature, Korean literature, period, poetry, Sichjo genre, genre, prose.